KEMUNDURAN MUTU IKAN BARONANG (Siganus javus) PADA PENYIMPANAN SUHU CHILLING - Mala Nurilmala; Nurjanah Nurjanah; Aisyah Fatriani; Afkar Rona Indarwati; Rizsa Mustika Pertiwi (Jurnal Teknologi Perikanan dan Kelautan, 2021)
Rabbitfish lives in waters of the mangrove to the reef at a depth of 6 meters. Rabbitfish usually is sold in a fresh condition. Generally, the low temperature has been used for fish handling technique to maintain its freshness. Thus, this study aimed to determine baronang fish quality deterioration from the Seribu Island using ice. The ratio of ice and fish was 1:1 (w/w). Determination of rabbitfish freshness was conducted by pH, TVB, and TPC measurements. Observation was every 24 hours for 3 days. The pH value decreased significantly at the 2nd day and the 3rd day. TVB value of rabbitfish on the first day was 10.57 mg N/100 g. This value indicated the fish was still fresh. However, the total number of microbes after 3 days of storage increased to 7.48 log CFU/g. Rabbitfish after 3 days storage was still suitable for consumption based on the pH and TVB values.